Combined metagenomic and phenomic approaches identify a novel salt tolerance gene from the human gut microbiome - Culligan, Eamonn P.; Marchesi, Julian R.; Hill, Colin; Sleator, Roy D. (Frontiers in Microbiology, 2014)
In the current study, a number of salt-tolerant clones previously isolated from a human gut metagenomic library were screened using Phenotype MicroArray (PM) technology to assess their functional capacity. One clone, SMG 9, was found to be positive for utilisation/transport of L-carnitine (a well-characterised osmoprotectant) in the presence of 6% w/v sodium chloride (NaCl). Subsequent experiments revealed a significant growth advantage in minimal media containing NaCl and L-carnitine. Fosmid sequencing revealed putative candidate genes responsible for the phenotype. Subsequent cloning of two genes did not replicate the L-carnitine-associated phenotype, although one of the genes, a σ54-dependent transcriptional regulator, did confer salt tolerance to Escherichia coli when expressed in isolation. The original clone, SMG 9, was subsequently found to have lost the original observed phenotype upon further investigation. Nevertheless, this study demonstrates the usefulness of a phenomic approach to assign a functional role to metagenome-derived clones.